2013
DOI: 10.1088/0957-4484/25/2/025701
|View full text |Cite
|
Sign up to set email alerts
|

One-to-one spatially matched experiment and atomistic simulations of nanometre-scale indentation

Abstract: We have carried out nanoindentation studies of gold in which the indenter is atomically characterized by field-ion microscopy and the scale of deformation is sufficiently small to be directly compared with atomistic simulations. We find that many features of the experiment are correctly reproduced by molecular dynamics simulations, in some cases only when an atomically rough indenter rather than a smooth repulsive-potential indenter is used. Heterogeneous nucleation of dislocations is found to take place at su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…MD simulations also suggested that material transfer usually occurs during contact separation [30]. A similar phenomenon was found by Oliver et al [100] when they performed one-to-one spatially matched experiment and atomistic simulations of nanometre-scale indentation; they reported that many features of the experiment were correctly reproduced by MD simulations, in some cases only when an atomically rough indenter rather than a smooth repulsive-potential indenter is used, tip wetting being one of these features. Paul et al [101] highlighted the need to further explore the role of adhesive forces and tip wetting, ranging from the mechanisms of substrate-to-tip material transfer to electronic transport properties.…”
Section: Role Of Adhesive Forces and Tip Wettingsupporting
confidence: 71%
“…MD simulations also suggested that material transfer usually occurs during contact separation [30]. A similar phenomenon was found by Oliver et al [100] when they performed one-to-one spatially matched experiment and atomistic simulations of nanometre-scale indentation; they reported that many features of the experiment were correctly reproduced by MD simulations, in some cases only when an atomically rough indenter rather than a smooth repulsive-potential indenter is used, tip wetting being one of these features. Paul et al [101] highlighted the need to further explore the role of adhesive forces and tip wetting, ranging from the mechanisms of substrate-to-tip material transfer to electronic transport properties.…”
Section: Role Of Adhesive Forces and Tip Wettingsupporting
confidence: 71%
“…We reach this conclusion from the experimental evidence of wire-drawing and the variable onset of repulsive contact loading with respect to the tunneling point. Results of molecular dynamics simulations for the same materials system also support the idea that gold is transferred to the tungsten tip during the indentation process [22].…”
Section: Saturation Behaviormentioning
confidence: 52%
“…For example, different tip−substrate adsorption behavior could be seen under UHV conditions, if not enough hydrogen is available to saturate the tip or if additional species preferentially react with the hydrogen and effectively remove it from the tip, or with different materials (as with the tungsten indenter on gold 12 ).…”
Section: Discussionmentioning
confidence: 99%